2013
DOI: 10.2174/1568026611313020007
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Dimethylarginine (ADMA): A Promising Biomarker for Cardiovascular Disease?

Abstract: Asymmetric Dimethylarginine (ADMA) is an endogenous inhibitor of nitric oxide (NO) production. ADMA is generated from methylation of arginine residues by protein arginine methyltransferases (PRMTs) and subsequent proteolysis, while its elimination is achieved mainly by degradation with dimethylarginine dimethylaminohydrolase (DDAH). Oxidative stress, endothelial nitric oxide synthase (eNOS) inhibition, eNOS uncoupling, inflammation and shear stress play a pivotal role in ADMA pathophysiology by managing PRMT/D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(61 citation statements)
references
References 0 publications
0
60
0
1
Order By: Relevance
“…1,[73][74][75][76][77] Thus, incremental NO reduction results in incremental ET-1 release, which contributes to several cardiovascular diseases. 1,77 Importantly, accurate modeling of the conditions required for endogenous NO-mediated decreased ET-1 release will allow further relevant investigation into potential interventions that reverse/ prevent the disruption of this negative regulatory pathway and, thus, eventual therapeutic modalities.…”
Section: Discussionmentioning
confidence: 99%
“…1,[73][74][75][76][77] Thus, incremental NO reduction results in incremental ET-1 release, which contributes to several cardiovascular diseases. 1,77 Importantly, accurate modeling of the conditions required for endogenous NO-mediated decreased ET-1 release will allow further relevant investigation into potential interventions that reverse/ prevent the disruption of this negative regulatory pathway and, thus, eventual therapeutic modalities.…”
Section: Discussionmentioning
confidence: 99%
“…This has been explained for the vasoconstriction and endothelial injury. A positive correlation of ADMA level and HHcy has been reported [2]. An increase in ADMA has been associated with approximately 4 fold increase in the risk for atherosclerosis [3].…”
Section: Role Of Hyperhomocysteinemia In Dementiamentioning
confidence: 88%
“…FGF-23 elevation plays a role in the pathogenesis of endothelial dysfunction [14,43], atherosclerosis [13], and left ventricular hypertrophy [44]. On the other hand, ADMA is an endogenous inhibitor of nitric oxide production and a promising biomarker for cardiovascular diseases [45]. To our knowledge, very few studies have reported the effect of TRT on ADMA levels in the literature.…”
Section: Discussionmentioning
confidence: 99%